DIRECT SCATTERING PROBLEM FOR MICROWAVE TOMOGRAPHY - Agung Tjahjo Nugroho (UPT Penerbitan Universitas Jember, 2016)
The Direct scattering problem is composed in a pair of integral equations. The equivalence current density and the ratio of dielectric contrast are set as variables by applying volume equivalence principle. The problem is solved using the method of moment (MM). The MM solutions are compared to the exact solutions. The results show that the MM solution is accurate. Perfect solution is generated for scattering from a wide range dielectric contrast. But, it is sensitive to cell’s size. A good result is provided at comparably small cell’s size.